Evaluasi Program Layanan Kesehatan Cageur Jasa di Puskesmas Tanah Tinggi Kota Tangerang - Irfan Dwi Septiawan; Ayuning Budiati; Nikki Prafitri (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
This study evaluates the Cageur Jasa Health Service Program at the Tanah Tinggi Public Health Center in Tangerang City, which was developed as an innovation to expand access to basic healthcare services through home visits. The program aims to improve service quality, strengthen family independence in maintaining health, and support the achievement of the 12 indicators of the Indonesia Healthy Program with a Family Approach (PIS-PK). The evaluation applies William N. Dunn’s six policy evaluation criteria effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness supported by theoretical frameworks from public administration, public policy, and health service innovation. This research employs a qualitative descriptive method, with data collected through observation, in-depth interviews with informants, and secondary data analysis. The findings indicate that the program’s implementation has not fully achieved its intended objectives, as evidenced by declining service coverage, several PIS-PK indicators remaining below 50%, increasing disease findings, and the persistence of maternal and infant mortality cases. Limitations in resources, coordination, infrastructure, and suboptimal promotive and preventive efforts further hinder the program’s effectiveness. Overall, the study concludes that although Cageur Jasa contributes to improving healthcare access, its implementation at the Tanah Tinggi Public Health Center remains suboptimal and requires continuous improvement.